2018
DOI: 10.1108/k-04-2017-0124
|View full text |Cite
|
Sign up to set email alerts
|

Operational challenges in collaborative research projects

Abstract: Purpose Collaborative research projects are highly complex organizational settings with specific needs and inherent risks that can endanger project success if not managed well. The purpose of this paper is to enlarge the knowledge of operational challenges in collaborative research projects to improve both project and conflict management. Design/methodology/approach On the basis of the concept of systemic conflict, this study conducts a conflict analysis of a collaborative research project on food security t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Furthermore, it is found that conflict drivers do not function in isolation, but interact (Löhr et al, 2018, Paper 1 (chapter 3.1, table 2)), making systemic perspectives on processes and management necessary (Löhr et al, 2018, Paper 1 (chapter 3.1, figure 2)).…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it is found that conflict drivers do not function in isolation, but interact (Löhr et al, 2018, Paper 1 (chapter 3.1, table 2)), making systemic perspectives on processes and management necessary (Löhr et al, 2018, Paper 1 (chapter 3.1, figure 2)).…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Projects are increasingly being established in response to calls for proposals, resulting in funding requirements directly impacting project consortia membership (Protogerou et al, 2010, Adler et al, 2009. This assumption of influence is supported by a study of interrelations between different conflict drivers in a transdisciplinary research project that finds that project design and implementation is heavily influenced by the donor agency's terms and conditions for funding (Löhr et al, 2018, Paper 1 (chapter 3.1)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…System dynamics, widely believed to be critical for handling the complexity facing the world, comprises a set of conceptual tools that enable understanding the structure and dynamics of complex systems [ 47 ]. In other words, system dynamics allows for taking a problem apart and reassembling it to understand its components and causal relationships [ 48 , 49 ]. CLDs are a useful tool within this approach, helping to provide a broad range of insights and implications [ 50 ] that can be used as the basis for developing actions and implementing policy [ 51 ].…”
Section: Methodsmentioning
confidence: 99%